The global oil market risks and uncertainties - Cordesman, Anthony H. 1939-2024; Al-Rodhan, Khalid R. (Significant issues series, 2006)
The goal of this study is to provide a risk assessment of the global oil market. Cordesman and Al-Rodhan study six major oil-producing regions of the world: the Middle East, Africa, Asia and the Pacific, Europe and Eurasia, North America, and South and Central America. In each case, the authors outline national oil developments and focus on four major areas of risks and uncertainties: macroeconomic fluctuations, geopolitical risks, oil production uncertainties, and the nature of resources.